Conditions of the Effective Formation of Legal Consciousness of Students By Means of Psychological Training - Muslumov, R; Pecherkina, A (KnE Life Sciences, 2018)
The article considers the conditions of the effective formation of legal consciousness of students through psychological training. The study included ascertaining and formative stages. 60 students aged 20 to 22 took part in it. At the ascertaining stage, R.R. Muslumov’s method of study of legal consciousness of personality was used to determine the levels of formation of the legal consciousness components of students. It was established that the formation of all components of legal consciousness among students (legal knowledge, legal attitudes, attitudes towards law, and attitudes toward legal institutions, legal activity and legal motivated cognition) was at an average and high level. At the formative stage, psychological training was used, which was aimed at developing legal consciousness and legal competence of students. The authors note that the most effective means of forming legal consciousness is psychological training based on the cognitive-behavioral approach, which suggests that a person can learn new social skills, emotions and new ways of thinking through the learning mechanism. Within the framework of the training, the work is focused on behavioral reactions and internal attitudes. As a result, qualitative positive results were obtained on the scales ”legal activity” and “motivated cognition”. Conditions for the effective formation of legal consciousness (which include interactivity, reality, relevance, success, emotionality and modernity) were generalized and identified in the group work. While recognizing the importance of educational work, the authors point out that the development of legal consciousness of students also depends on other external (family, conditions in a particular university, friends, etc.) and internal (character, personality characteristics, etc.) factors. It is not enough simply to form legal knowledge - it is important to nurture the legal consciousness, legal beliefs, lay the foundation of behavior on the basis of law observance. Keywords: Legal consciousness, legal competence, legal activity, legal socialization, legal motivated cognition, legal attitudes, psychological training.